The Influence of Social Media Marketing, Product Quality, and E-Word of Mouth on the Purchase Decision of Jiniso Fashion Products - Septi Herawati; Evan Saktiendi; Belinda Permata Putri (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to determine the partial and simultaneous influence between the variables of Social Media Marketing, Product Quality, and E-Word of Mouth on the Purchase Decision of Jiniso fashion products. The analysis method used in this study is quantitative primary data, the test stages carried out are: Validity Test, Reliability, Normality, Heteroscedasticity, Multicollinearity, Multiple Linear Regression, Partial Test (t Test), Simultaneous Test (F Test), and Coefficient of Determination (R2). The data used in this study used a questionnaire instrument of 100 respondents. The sampling method used is the non-probability sampling method, using the purposive sampling technique. The testing tool used is SPSS version 30. The results of the study indicate that the variables of Social Media Marketing, Product Quality, and E-Word of Mouth partially and simultaneously influence the Purchase Decision of Jiniso fashion products.